2011
DOI: 10.1007/s11096-011-9597-8
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation control of pharmacist-managed collaborative care versus usual care in Thailand

Abstract: Pharmacist-managed warfarin therapy resulted in a significantly better anticoagulation control. This study showed that a collaborative approach in anticoagulation management can be successfully implemented in a developing country. Implementation of such care model in other developing countries should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 28 publications
1
42
2
Order By: Relevance
“…Whereas, Witt et al study that included 6645 patients reported significant higher TTR in clinical pharmacy anticoagulation service group compared with usual care (63.5% vs 55.2%, p<0.001) which was other from RCTs pooled results in our study (12). The similar results reported in several studies that time in the INR therapeutic range was 48.1%~78.5% in pharmacist management group while 4.01%~66.2% of other management models (27,28,32,41,42,44,45). Most of opposite results came from retrospective chart review studies and our results from RCTs grading as moderate quality evidence were more convictive.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Whereas, Witt et al study that included 6645 patients reported significant higher TTR in clinical pharmacy anticoagulation service group compared with usual care (63.5% vs 55.2%, p<0.001) which was other from RCTs pooled results in our study (12). The similar results reported in several studies that time in the INR therapeutic range was 48.1%~78.5% in pharmacist management group while 4.01%~66.2% of other management models (27,28,32,41,42,44,45). Most of opposite results came from retrospective chart review studies and our results from RCTs grading as moderate quality evidence were more convictive.…”
Section: Discussionsupporting
confidence: 78%
“…A couple of studies indicated that the percentage of time within the expanded therapeutic range of patients in pharmacist-led management group were significantly higher than of control group (26,41,42), which was up to 90.8% in pharmacist management group from Young et al study (90.8% vs 84.8%, p<0.0001) (32). Although, no publication bias and serious heterogeneity were detected in RCTs and observational studies of INR control, inadequate studies and sample size arrived at poor results.…”
Section: Discussionmentioning
confidence: 99%
“…28 Our TTR values were also similar to studies developed in other tertiary hospitals (from 53.9% to 65.1%). [29][30][31] INR/current dose ratio was also significantly higher in the group of patients taking amiodarone compared with patients who did not take amiodarone. This ratio is a simple and logical way of expressing the variability of INR response to the different warfarin doses according to amiodarone use.…”
Section: Tablementioning
confidence: 82%
“…We planned a study using continuous response variables from independent usual care and intervention subjects with one instance of usual care per intervention subject. In a previous study (12), the response within each group was normally distributed with standard deviation (SD) of 8.5. If the true difference between the intervention and usual care means is 8.2, we would require 18 subjects per group to be able to reject the null hypothesis that the population means of the Intervention and Usual care groups are equal with probability (i.e., power) of 0.8.…”
Section: Sample Size Calculationmentioning
confidence: 99%